2013
DOI: 10.1371/journal.pone.0081134
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cell Surface Free Thiols Identify Effector CD8+ T Cells Undergoing T Cell Receptor Stimulation

Abstract: Recognition of peptide Major Histocompatibility Complexes (MHC) by the T cell receptor causes rapid production of reactive oxygen intermediates (ROI) in naïve CD8+ T cells. Because ROI such as H2O2 are membrane permeable, mechanisms must exist to prevent overoxidation of surface proteins. In this study we used fluorescently labeled conjugates of maleimide to measure the level of cell surface free thiols (CSFT) during the development, activation and differentiation of CD8+ T cells. We found that during developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…Glutathione adds via conjugate, 1,4-addition, and coenzyme-A (CoA) reacts with fumarates only via acylation (or 1,2-addition), see reactions marked A and B, Figure 1 . Thereafter, fumarate-CoA-adducts form Krebs cycle metabolites in cells, however, formation and fate of conjugate 1,4-addition products of CoA with fumarates are unknown in animal biochemistry literature [ 30 , 31 ].…”
Section: Mini Reviews On the Roles Of Dmf Bupropion Same And VImentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione adds via conjugate, 1,4-addition, and coenzyme-A (CoA) reacts with fumarates only via acylation (or 1,2-addition), see reactions marked A and B, Figure 1 . Thereafter, fumarate-CoA-adducts form Krebs cycle metabolites in cells, however, formation and fate of conjugate 1,4-addition products of CoA with fumarates are unknown in animal biochemistry literature [ 30 , 31 ].…”
Section: Mini Reviews On the Roles Of Dmf Bupropion Same And VImentioning
confidence: 99%
“…Upon combining with cytoplasmic Nrf2 protein, the glutathione-thiosuccinate-Nrf2 complex is expected to migrate into the nucleus, activate the antioxidant defense system genes, and generate antioxidants (glutathione, superoxide dismutase, and catalase) that quench free radicals, avert oxidative stress, subdue inflammation, and preclude NLRP3 inflammasome mediated pyroptosis [ 24 , 25 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Mini Reviews On the Roles Of Dmf Bupropion Same And VImentioning
confidence: 99%
“…There is evidence that post translational control of disulfide bond topology also plays a role in regulation of the immune system. Activation of T cells results in up regulation of thioredoxin-1 (Trx1), a ubiquitous thiol reductase enzyme [ 14 ], and results in increased thiols at the T cell surface [ 15 , 16 ], which can be inhibited with thiol reductase inhibitors [ 15 ]. Activated dendritic cells also secrete Trx1 [ 17 ] which can reduce disulfide bonds at the surface of both the dendritic cells and co cultured T cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, controlling this modulation provides a potential means of therapeutic intervention of many diseases, such as those involving the immune system [ 13 ], haemostasis [ 12 ] and cancer [ 35 ]. An increase in free thiols on immune cells upon activation was first described 20 years ago by Lawrence et al [ 33 ] and was henceforth confirmed in various studies [ 36 38 ]. However, these studies are limited as they only provide global data and do not identify the modified proteins, nor do they provide a quantitative determination of the level of reduction of each protein.…”
Section: Discussionmentioning
confidence: 63%
“…Similar effects were observed by Lawrence et al [ 33 ] using PMA (independent of antigen presentation) to stimulate PBMCs and the ubiquitous thiol isomerase inhibitor bacitracin. Although it was previously shown that Trx1 and other oxidoreductases are upregulated and secreted from T cells upon activation [ 38 , 40 ], we provide the first global identification of the proteins containing labile disulfide bonds sensitive to oxidoreductases on the surface of T cells undergoing activation and expansion. The self-modulation of cell surface receptors by labile disulfide bond reduction is a concept analogous to the autocrine function of cytokines.…”
Section: Discussionmentioning
confidence: 99%